The effect of microRNA-145 on proliferation and apoptosis of cutaneous squamous cell carcinoma cells - Gengjian Zhang; Songlian Lei; Kaiyue Zhang (Discover Oncology)
Abstract Objective This study aimed to explore the effects of microRNA−145 (miR−145) on the proliferation, cell cycle distribution, and apoptosis of cutaneous squamous cell carcinoma (CSCC) A431 cells. Methods A431 cells were transfected with miR−145 mimics and negative control microRNA using Lipofectamine 2000. The experiments were divided into three groups: the miR−145 mimics transfection group, the negative control microRNA transfection group, and the blank control group (without any treatment). Results The expression levels of miR−145 were significantly higher in the miR−145 mimics group than in the negative control microRNA group and the blank control group (p < 0.01). The cell proliferation level of the miR−145 mimics group was significantly lower at 24 h, 48 h, and 72 h post-transfection compared to the negative control microRNA group and the blank control group (p < 0.01). The proportion of cells in the G0/G1 phase was significantly higher in the miR−145 mimics group, while the percentage of cells in the S phase was significantly lower (p < 0.01). Additionally, the apoptosis rate in the miR−145 mimics group was significantly higher than that in the negative control microRNA group and the blank control group (p < 0.01). The relative expression levels of Caspase−9 and Caspase−3 were also significantly higher in the miR−145 mimics group (p < 0.01). Conclusion Upregulation of miR−145 expression by miR−145 mimics transfection in CSCC A431 cells significantly inhibited cell proliferation, blocked cell cycle progression at the G0/G1 phase, and promoted apoptosis by increasing the expression of apoptotic proteins Caspase−9 and Caspase−3. These findings suggest that miR−145 may serve as a potential anti-tumor factor in CSCC, highlighting its potential as a therapeutic target for future research.